An analysis of numeracy problem-solving difficulties among seventh-grade students in PISA-type tasks - Jari, Wilburga Laong Leony; Asri, Maria Angelina; Wewe, Melkior (Desimal: Jurnal Matematika, 2025)
Education serves as a fundamental foundation for developing high-quality and competitive human resources and plays a strategic role in supporting sustainable development. Within the framework of the Sustainable Development Goals (SDGs), quality education is positioned as Goal 4, which aims to ensure inclusive, equitable, and quality education while promoting lifelong learning opportunities for all. In line with this objective, this study focuses on analyzing the difficulties experienced by seventh-grade students at SMP Negeri 1 Bajawa, Ngada Regency, in solving PISA-type numeracy problems. The study not only identifies students’ levels of numeracy literacy but also examines in depth the difficulties encountered at each stage of the problem-solving process. A mixed methods approach with a sequential explanatory design was employed, beginning with the collection and analysis of quantitative data to determine students’ numeracy literacy levels, followed by qualitative data collection and analysis to explore the types, stages, and factors contributing to students’ difficulties in solving PISA-type numeracy problems. The results indicate that the numeracy literacy skills of seventh-grade junior secondary school students remain at low to moderate levels, particularly when solving PISA-type numeracy tasks that require contextual understanding and mathematical modeling. Among the stages of problem solving, mathematical modeling emerged as the most challenging, as many students were unable to connect contextual situations with relevant mathematical concepts or construct appropriate mathematical representations.